GAME EDUKATIF BERMUATAN NILAI MORAL UNTUK MENANAMKAN KERJA SAMA SISWA KELAS 3 SD - Budiarti, Meylingga; Prastika, Varenezza; Sitarianti, Tiyas Febbi; Zahro, Hani Muslihatun; Hayati, Auliya Aenul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study developed and tested the effectiveness of a moral values-based snakes and ladders game to improve the cooperation skills of third-grade elementary school students. Using a quantitative approach with a quasi-experimental design, the study involved 21 third-grade students from SDN 1 Kalikoa. The “Great Team Mission” learning media was developed by integrating Living Values Education (LVE) values into a modified snakes and ladders game. The research instruments consisted of a Likert-scale cooperation questionnaire, a collaborative activity observation sheet, and a media feasibility questionnaire. Data were analyzed using descriptive statistics. The results showed that the implementation of the game significantly improved students' collaboration skills. Students underwent a transformation from individualistic attitudes to more collaborative, communicative, and empathetic ones. The game's mechanism, featuring a collaboration point system and group challenges, proved effective in forcing students to collaborate and create positive interdependence. This media also enhanced learning motivation and social interaction in a fun atmosphere. The study provides practical contributions for educators in implementing game-based learning aligned with the Merdeka Curriculum and the Pancasila Student Profile, particularly the dimension of mutual cooperation ABSTRAKPenelitian ini mengembangkan dan menguji efektivitas game ular tangga bermuatan nilai moral untuk meningkatkan kemampuan kerja sama siswa kelas 3 SD. Menggunakan pendekatan kuantitatif dengan desain eksperimen semu, penelitian melibatkan 21 siswa kelas 3 C SDN 1 Kalikoa. Media pembelajaran